Culture, power and identity; The case of Ang Hien Hoo, Malang - Budianta, Melani (Wacana, Journal of the Humanities of Indonesia, 2017)
This paper discusses the intricate relations between culture and identity in a web of larger power structures of politics and the market by looking at the ways in which the Indonesian Chinese attach themselves to a local performing arts tradition. The paper focuses on the history of the wayang orang amateur club called Ang Hien Hoo in Malang, East Java, which emerged from a Chinese diaspora burial association, to attract national limelight in the 1950s and 1960s. In this paper, I see this amateur club as a site, not only for cultural assimilation, but also as a meeting space for the diverse migrant Chinese population residing at a host country. The space is used to negotiate their position as citizens responsible to promote and to become patrons of local traditional performing arts. The paper examines how this amateur club was swept by the Cold War politics and national political turmoil of 1965, and how it fought to survive under the pressures of the global capitalist era. What emerges from the findings is the contradictory fact that the identification of the Chinese with the Javanese traditional performing arts is affirmed precisely as it is marked by Chineseness. Thus, despite the cultural blending, the Chinese Indonesian's patronage of local traditional art continuously reproduces the double bind of making home in the culture not seen as their own.